Deposition behaviors and interfacial interaction mechanism between carboxyl-modified polystyrene nanoplastics and magnetite in aquatic environment - Meimei Ran; Xin Nie; Jingxin Wang; Ruiyin Xie; Xiaoping Lin; Hanjun Zhu; Quan Wan; Yuhong Fu (Ecotoxicology and Environmental Safety)
In aquatic environments, the deposition behaviors of nanoplastics (NPs) are closely associated with interfacial interaction between NPs and iron (hydr)oxides minerals, which are typically coupled with solution chemistry and organic matter. However, the roles of solution chemistry and organic matter in the deposition behavior of NPs with iron (hydr)oxides minerals and related interfacial interaction mechanism are still poorly understood. In this study, the deposition behaviors of carboxyl-modified polystyrene nanoparticles (COOH-PSNPs) with magnetite were systematically investigated. The results showed that electrostatic attraction, hydrogen bond, and charge-assisted hydrogen bond (CAHB) were the main forces for the deposition and interfacial interaction mechanism between COOH-PSNPs and magnetite. Increasing pH could significantly inhibit the deposition of COOH-PSNPs with magnetite. At pH 6.5, phosphate and dichromate significantly inhibited the deposition of COOH-PSNPs since their competitive adsorption for the surface sites on magnetite led to a potential reversal of magnetite, resulting in the strong electrostatic repulsion between COOH-PSNPs and magnetite. Moreover, when the concentration of phosphate exceeded 0.01 mM, the deposition of COOH-PSNPs was completely hindered. Organic macromolecules (OMs) markedly inhibited the interfacial interaction and deposition of COOH-PSNPs with magnetite by enhancing the electrostatic repulsion and steric hindrance between COOH-PSNPs and magnetite due to the formation of magnetite-OM associations. The inhibition abilities followed the order sodium alginate (0.1 mM) > humic acid (0.2 mM) > bovine serum albumin (5 mM). This study may provide insights for better understanding of environmental behaviors of COOH-PSNPs associated with magnetite and organic matter in natural environments at the molecular level.